Caracterización física y química del embalse Riogrande II (Antioquia), Colombia (2015)
ABSTRACT: In this investigation Riogrande II reservoir is characterized from the climatic, chemical, and physical perspectives. With this aim were measured two climatic variables (rainfall and wind), six physical (temperature, vertical attenuation for upwelling irradiance, suspended solids, dissolved solids, turbidity, electrical conductivity) and four chemical (dissolved oxygen, free CO2, pH, alkalinity). These quanti cations were carried out along one year in ve sampling stations between which río Chico arriba was signi cantly different due to high degree of material in suspension and high values for all of the descriptors measured, was different to the others. In the gravity-light axis the reservoir was strati ed with upwelling of metalimnetic water inside the surface layer, and anoxic hipolimnio during the entire sampling year in all the sampling points. It is considered that the reservoir has an atelomictic mixture pattern.